The impact of inter-annual weather variations on energy storage and flexible generation – a UK case study - Öberg, Simon; Johnsson, Filip; Odenberger, Mikael (Energy (Oxford), 2025)
Traditionally, energy systems modeling has relied on a single ‘representative’ meteorological year as basis for modeling of future energy systems. However, with growing shares of weather-dependent electricity generation, accounting for inter-annual variability has become increasingly important. This study applies a three-step modeling framework to examine how inter-annual weather variations affect investment and operation of electricity generation and storage technologies, with a particular focus on the interplay between batteries and flexible generation, as well as associated revenue streams in a future electricity system. The results show that while the annual capacity factor for wind power influences overall investment levels – where a lower capacity factor leads to greater wind power deployment – this metric has limited relevance for the investment and use of batteries and flexible generation. Instead, short-term variability more strongly affects the optimal deployment of storage and dispatchable generation across different meteorological years. These findings highlight the necessity of high temporal resolution in capacity expansion modeling to accurately assess system adequacy under high shares of variable electricity generation. Regarding revenue streams, open-cycle gas turbines face the greatest difficulty in recovering costs via the energy-only market, underscoring the need for complementary revenue streams or market mechanisms to support their role in covering infrequent but critical energy shortfalls. •Wind capacity factors impact mainly investments in bulk electricity generation.•No correlation between VRE capacity factors and investments in flexible generation.•Individual years with biomass demand up to three times the 10-year average.•Also the Year 2018 could be considered as a representative year.•Annual electricity cost ranges from 97 €/MWh to 29 €/MWh.